ANALISIS PERKEMBANGAN EMOSIONAL ANAK USIA 5-6 TAHUN DI TK NURUL YAQIN - Rifdah, Anisa; Sit, Masganti (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Emotional development in children aged 5-6 years is a critical stage in the formation of their mental and social well-being. Environmental factors, social interactions, and the child's understanding of emotions play an important role in this process. This research aims to explore emotional regulation strategies, environmental and parenting factors that influence emotional development, the influence of social interactions, and children's understanding of emotions in children aged 5-6 years. This research uses observation and interview methods to collect data regarding children's experiences in managing their emotions, social interactions, and their perceptions of emotions. Data was analyzed using a qualitative approach to gain an in-depth understanding of this topic. The research results show that children aged 5-6 years begin to develop various strategies to regulate their emotions, including verbal and non-verbal expressions. Environmental and parenting factors, such as emotional support from the family, play an important role in shaping children's emotional responses. Social interactions with peers also contribute significantly to their emotional development. In addition, children begin to understand their own emotions and those of others, although this is still a learning process.